DESIGN AND IMPLEMENTATION OF A MANAGEMENT INFORMATION SYSTEM FOR MARKETING TOOLS INVENTORY AND SCHOOL PRESENTATION HONORARIUM RECAPITULATION AT LP3I NORTH JAKARTA (POLITEKNIK LP3I JAKARTA, 2026)
Design and Development of a Management Information System for Marketing Tools Inventory and School Presentation Honorarium Recapitulation at LP3I North Jakarta is a system designed to facilitate the management of inventory, honorarium records, and presentation schedules by authorized personnel. The system was developed as a computerized solution to improve the quality of services provided to staff while simplifying the management of inventory data, honorarium disbursement records, and scheduling processes compared to the previous manual system. The development of this system was based on several research methodologies, including interviews, observations, and literature review. The system was implemented using the CodeIgniter framework due to its efficiency, flexibility, and ease of maintenance during the development process. The existing inventory management, honorarium recapitulation, and presentation scheduling system at LP3I North Jakarta still relies on manual procedures, which are prone to calculation errors, data loss, and reduced reliability. Therefore, the implementation of the proposed system is expected to support the operational activities of the marketing and finance departments more effectively. Furthermore, the system is anticipated to improve the efficiency and effectiveness of marketing and finance personnel in managing inventory, honorarium records, and presentation schedules.